2007
DOI: 10.1111/j.1467-8519.2007.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and End‐of‐life Decision Making: Comparison of Japanese and Japanese‐american Focus Groups

Abstract: Variation in decision-making about end-of-life care among ethnic groups creates clinical conflicts. In order to understand changes in preferences for end-of-life care among Japanese who immigrate to the United States, we conducted 18 focus groups with 122 participants: 65 English-speaking Japanese Americans, 29 Japanese-speaking Japanese Americans and 28 Japanese living in Japan. Negative feelings toward living in adverse health states and receiving life-sustaining treatment in such states permeated all three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
92
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 40 publications
1
92
1
Order By: Relevance
“…The relationship of the primary decision maker to the patient may affect treatment intensity. The family's treatment preferences may also be influenced by culture or filial responsibilities, 69,76,77 as well as their own assessment of the patient's quality of life or likelihood to benefit from treatment. Lastly, just as the patients' characteristics may affect their preferences, the surrogates' characteristics and experiences may also influence preferences.…”
Section: Family Preferencesmentioning
confidence: 99%
“…The relationship of the primary decision maker to the patient may affect treatment intensity. The family's treatment preferences may also be influenced by culture or filial responsibilities, 69,76,77 as well as their own assessment of the patient's quality of life or likelihood to benefit from treatment. Lastly, just as the patients' characteristics may affect their preferences, the surrogates' characteristics and experiences may also influence preferences.…”
Section: Family Preferencesmentioning
confidence: 99%
“…The United Sates is a nation increasingly composed of people with diverse racial or ethnic and cultural backgrounds. Decision making for end-of-life care in a cross-cultural context can be difficult because these decisions must be understood within cultural beliefs and values (2). With increasing diversity in the United States, conflicts between patients and physicians who have different backgrounds are becoming common.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, the health care system is based on the concept of respect for autonomy and the patient's right to self-determination (1). Since many patients lose decision-making ability when they become seriously ill, advance care planning has been widely used in the United States to preserve autonomy in end-of-life decisions (2). In addition, advance care planning is promoted to ease medical care toward the end of life (3).…”
Section: Introductionmentioning
confidence: 99%
“…Although patients vary in the degree to which they want to be medically informed and to thereby participate in the decision-making process, surveys of patient preferences indicate that the overwhelming majority of patients in Western countries [11][12][13][14][15][16][17][18][19], and substantial proportion of patients in nonWestern countries [13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], want disclosure of information to participate in the decision-making process. Universally, recent survey data of patient preferences demonstrate substantial heterogeneity of preferences that are not individually predictable by geography, culture, age, race, sex or educational level [11][12][13][14][15][19][20][21][22][23][24][25][26][27][28][29][30]…”
mentioning
confidence: 99%
“…Universally, recent survey data of patient preferences demonstrate substantial heterogeneity of preferences that are not individually predictable by geography, culture, age, race, sex or educational level [11][12][13][14][15][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]39]. Furthermore, studies that have evaluated the concordance between patient preferences on one hand and family member perception of patient preferences on the other hand have demonstrated that family members commonly underestimate the amount of information that patients desire about their condition and the degree to which they want to be involved in decisionmaking [32,37,[40][41][42][43][44].…”
mentioning
confidence: 99%